Motivational Tendency Differences Between the Pre-qin Confucianism and Legalism by Psycholinguistic Analysis - Hu, Bo; Fan, Miaorong; Huang, Feng; Zhu, Tingshao (Frontiers in Psychology, 2021)
Among the hundred schools of thought that flourished during the pre-Qin era, Confucianism and Legalism are the most important ones as their thoughts cast a longstanding influence on the Chinese culture—cultural-psychological formation of the Chinese people. Most of the previous researches focused on analyzing the similarities and differences of the thoughts of Confucianism and Legalism, and few of them analyzed their motivational tendencies. This paper conducted a word frequency analysis of pre-Qin Confucian and Legalist classics with CC-LIWC, an independently developed program for classical text analysis, and made comparative research into the motivational tendencies of the two schools of thought in terms of psycholinguistic differentials. According to our research results, the use of words representing power (M=0.1377, SD=0.0104, p=0.014) and reward (M=0.0151, SD=0.0042, p=0.037) is more frequent in Legalist classics than in Confucian classics, whereas the use of words representing affiliation (p=0.066), risk (p=0.086) and achieve (p=0.27) shows no significant difference between Confucian and Legalist classics. This paper believes that both Confucianism and Legalism are mainly motivated by power, which is the most distinct feature of their motivational tendencies, and that Legalism is more motivated by power and reward than Confucianism; both Confucianism and Legalism are outcomes of the monarchy society with the former showing the reserved side of monarchy and the latter showing the uninhibited side of monarchy; an effective political methodology is absent in Confucianism, while utilitarianism constitutes the cornerstone of the political philosophy of Legalism.